Muscle belly in the tunnel: an unusual cause of carpal tunnel syndrome in a patient with spinal cord injury - (:unkn) unknown (SPRINGERNATURE, 2019)
Introduction Carpal tunnel syndrome, entrapment of median nerve at the wrist, is one of the most commonly encountered peripheral neuropathies in the upper extremity. It is also common in individuals with spinal cord injury due to repetitive movements during wheelchair use. Although it is well known that prevalence of carpal tunnel syndrome is high in individuals with spinal cord injury, no previous study identified aberrant muscle as the cause. Case presentation A 43-year-old man with T10 incomplete, ASIA Impairment Scale (AIS) C, patient with paraplegia who is a wheelchair basketball player presented to our electrodiagnostic laboratory with complaints of bilateral hand numbness after intensive training for a local veteran wheelchair basketball tournament. Nerve conduction studies showed carpal tunnel syndrome. Ultrasonographic assessment of carpal tunnel revealed the presence of abnormal muscle in the carpal tunnel encroaching the median nerve dynamically. Discussion It is important to identify the underlying cause of carpal tunnel syndrome, which is a common cause of upper extremity impairment in individuals with spinal cord injury because individuals with spinal cord injury who use wheelchair depend on their arms for mobility, transfers, and most activities of daily life.